الجسد الأنثوي ودلالته الرمزية في قراءات - قنيفة, نورة (Changement Social; No 4 (2018): revue change social, 2018)
أنلكلإن قراءات عديدة لأبحاث أنثروبولوجية هامة جدا منها بيار بورديو في "هيمنته الذكورية"، كاميل لاكوست دو جاردان في"أمهات ضد نساء"، سمية نعمان قسوس في "بلا حشومة"، مريم بوزيد وقراءاتها للمرأة الترقية وغيرها من القراءات عكس-لاتزال- قوّة معرفية أنثروبولوجية معمّقة من جهة، ومرجعية فكرية تحليلية هامة جدا من جهة أخرى كثيرا ما ساهمت في تحليلاتنا لموضوع المرأة ... ولعل مجرد الحديث عمّا هو في اعتقادنا "رد اعتبار" علمي لباحثات قدّمن الكثير في مجتمعات محلية لا تزال تعيش وتتعايش مع الكثير من المتناقضات المجتمعية بفعل تأثير الثقافات الدخيلة في مقابل هيمنة معادلة الجنس/المقدس على المخيال الاجتماعي،بل وترفض هذه المجتمعات الاعتراف الاجتماعي بها أو الخروج عنها مما يجعل من ممارسة أي اقتراب اجتماعي أنثروبولجي صعبا جدا لدرجة المغامرة .. هي أيضا في اعتقادنا جرأة بحثية خصوصا في علاقتها بالجسد الأنثوي وما ارتبط به من طابوهات في ظل مقاومة شعبوية لكل ما يتعلق بطابو الجسد ومرجعياته المجتمعية المنبثقة من الشرف والحشمة والعيب والعار.. والتي تعكس خصوصية الجسد الذي يصعب تحديد هويته خارج إطار معالم المعادلة ، خصوصية على الرغم من تباين مفرداتها والتي منها: العذرية، الزواج، التنشئة الاجتماعية، المقدس، والمحرّمات..إلاّ أنها تشير إلى ارتباط حيوي يربط المرأة كذات بالآخر من خلال المحدّد الزمكاني وفعل التفاعل الاجتماعي الدائم والمستمر مع المحيط الاجتماعي بحيثياته المختلفة.. ولعل الأصعب في كل هذا اعتماد تقنيات تتطلب كل أشكال الحضور لدراسة التراث اللامادي... As In many reviews of very important anthropological researches among which those of Pierre Bourdieu in “His manhood domination”, Camille Lacoste du Jardin in “Mothers against women”, SoumayaNaamaneGuessous in “Without shame”, and MeriemBouzid and her reviews of the Tuareg women and other reviews that had reflected and -still do- a powerful deep and very important analytical  anthropological knowledge from one side ,and referential thoughts  from the other side , that  had participated in our analysis of the woman’s subject.     Perhaps talking about what we believe to be a scientific return of esteem to researchers who gave a lot in our local societies , still live and cohabitate with many social inconsistencies due to the impact of exterior cultures face to the domination of gender/sacred equation on the social imagination , These societies even refuse its social recognition or abandon  it, which makes any implementation or social  anthropological approach  very difficult  and even an adventure.     Which we believe also to be a scientific enterprise as it is  related to the female body and the taboos which goes with , in front of  a popular resistance to anything to do with  body taboos and its social references emanated from honor, shyness, shame, and dishonor …which reflects the particularity of the body and the difficulty to determine its identity outside parameters of equivalence, a particularity added to its varied words such :virginity, marriage, socialization , sacred, religious bans…But it indicates a vital relations  that ties woman as an entity  with the other ,through time determinants and social permanent interaction with the social environment and its different aspects, and  may be the at most difficulty of all of that resides in the use and the techniques that require all forms of presence to study immaterial heritage…